1990
DOI: 10.1159/000174702
|View full text |Cite
|
Sign up to set email alerts
|

Ibopamine in the Treatment of Mild Chronic Heart Failure in Elderly Patients

Abstract: This double-blind, randomized, multicenter clinical study assessed the efficacy and safety of ibopamine 100 mg t.i.d. as monotherapy vs. placebo in 52 patients with mild chronic heart failure aged over 60 years during a 12-week treatment period. Ibopamine produced a statistically significant increase in exercise tolerance and reduction in fatigue during effort compared to placebo. A trend towards decreased requirement of concomitant diuretic therapy was noted in the ibopamine-treated group. Ibopamine was well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…These results support those of the multicenter evalua tion of a larger number of patients using the same proto col [13]. The present results are also consistent with those of another large double-blind trial [26], showing a statistically significant improvement in exercise time; the magnitude of the effects was the same in both stud- female female male male female male female female female female male male female female male male female 21 54 placebo placebo placebo placebo placebo placebo placebo placebo ibopamine ibopamine ibopamine ibopamine ibopamine ibopamine ibopamine ibopamine ibopamine 100 15 24 69 25 25 59 26 130 155 27 During the same period as this study was conducted, 20 patients, comparable to our sample in terms of demo graphic and clinical characteristics, were treated with captopril for 12 weeks at 25 mg three times daily, adopting similar procedures as described in the present trial (unpublished data).…”
Section: Clinical Efficacy and Safetysupporting
confidence: 86%
See 1 more Smart Citation
“…These results support those of the multicenter evalua tion of a larger number of patients using the same proto col [13]. The present results are also consistent with those of another large double-blind trial [26], showing a statistically significant improvement in exercise time; the magnitude of the effects was the same in both stud- female female male male female male female female female female male male female female male male female 21 54 placebo placebo placebo placebo placebo placebo placebo placebo ibopamine ibopamine ibopamine ibopamine ibopamine ibopamine ibopamine ibopamine ibopamine 100 15 24 69 25 25 59 26 130 155 27 During the same period as this study was conducted, 20 patients, comparable to our sample in terms of demo graphic and clinical characteristics, were treated with captopril for 12 weeks at 25 mg three times daily, adopting similar procedures as described in the present trial (unpublished data).…”
Section: Clinical Efficacy and Safetysupporting
confidence: 86%
“…Monotherapy with ibopamine was associated with a good tolerability and no evidence of arrhythmogenic potential. It was concluded that ibopamine as monotherapy was clinically efficacious in these elderly patients with mild heart failure.This study is an extension of a previously reported study designed to compare the clinical efficacy of dopa mine against placebo in elderly patients with mild con gestive heart failure (CHF), with the primary efficacy criterion being exercise tolerance [13].In the present study the influence of treatment with dopamine on plasma catecholamine and aldosterone concentrations was also measured in a subset of pa tients. …”
mentioning
confidence: 98%
“…In most noncomparative and placebo-controlled studies, ibopamine was administered with concomitant medication, including diuretics, digoxin and/or vasodilators, although in some instances the use of digoxin (Azzolini et al 1990) and vasodilators [excluding short acting nitrates (Condorelli et al 1989;Fazio et al 1990)] was prohibited Dalla Volta et al 1991;de Ritis et al 1991;Pizzomi et al 1991). While predominantly of short to medium duration (4 weeks to 6 months), some trials have evaluated longer term (up to 2 years) ibopamine therapy.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
“…Recently, with respect to the clinical bene fits of ibopamine on chronic heart failure, there has been an emphasis not only on its safety [21 ] and effectiveness [22,23] as a cardiostimulator. but also on its vasodilating properties [24][25][26][27], Other studies have re ported that ibopamine improves abnormali ties induced by cardiac disease in the sympa thetic nerve system, renin-angiotensin system and antidiuretic hormones [28],…”
Section: Discussionmentioning
confidence: 99%
“…The hemodynamic effects of such high ibopamine doses have been analyzed [ 12], Some recent studies [ 12,22,23,33,36,[39][40][41] suggest that 100 mg t.i.d. constitutes the optimal ibopamine dose in terms of clinical efficacy and safety in the long-term treatment of ibopaminc.…”
Section: Discussionmentioning
confidence: 99%